The World’s largest known Gorgonian - Watling, Les; Rowley, Sonia; Guinotte, John (Zootaxa, 2013)
Gorgonians in the deep sea can be much larger than their shallow water counterparts, but there are only a few scattered measurements. We have estimated the size of a chrysogorgiid gorgonian, Iridogorgia magnispiralis Watling 2007, observed from a submersible on Twin Banks in theNorthwest Hawaiian Islands, as being 5.7 m tall.